Alternativas para la estabilización de taludes en el cantón de León Cortés - Ugalde-Madrigal, Karla Fabiola (Instituto Tecnológico de Costa Rica., 2015)
This project is to provide comprehensive solutions to the problems of slope stabilization, due to the geomorphology of the canton of Leon Cortes, as it is characterized by a topography of steep slopes and high precipitation intensity. Objectives is to design a retaining wall in masonry and gabion wall for slope stabilization; also performing their respective construction process and budget. To do this, it aims to collect data in the area (National Emergency Commission, Instituto Costarricense de Electricidad and the Internet), as well as bibliographic information and topics to be developed based on the national legislation make a calculation. It is intended to use the Excel program and Geo5; for designing walls. In conclusion when comparing both walls, economically important differences are estimated, as both designs were performed under the same conditions, which varies in the choice, it is the area that is available for the project.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2015.
Keywords: Drenaje; Muros de contención; Suelos; Mampostería